Fixed Point Theorems for Generalized F-contraction on Metric Space - Barman, Dinanath; Tiwary, Kalishankar (Sarajevo Journal of Mathematics, 2022)
In this paper, we have generalized F-contraction to MF-contraction, a new of notation in metric space and we have proved some results with examples and corollaries.